A High-Throughput BRET Cellular Target Engagement Assay Links Biochemical to Cellular Activity for Bruton's Tyrosine Kinase. (February 2020) - Ong, L. L.; Vasta, J. D.; Monereau, L.; Locke, G.; Ribeiro, H.; Pattoli, M. A.; Skala, S.; Burke, J. R.; Watterson, S. H.; Tino, J. A.; Meisenheimer, P. L.; Arey, B.; et al.
Protein kinases are intensely studied mediators of cellular signaling. While traditional biochemical screens are capable of identifying compounds that modulate kinase activity, these assays are limited in their capability of predicting compound behavior in a cellular environment. Here, we aim to bridge target engagement and compound-cellular phenotypic behavior by utilizing a bioluminescence resonance energy transfer (BRET) assay to characterize target occupancy within living cells for Bruton's tyrosine kinase (BTK). Using a diverse chemical set of BTK inhibitors, we determine intracellular engagement affinity profiles and successfully correlate these measurements with BTK cellular functional readouts. In addition, we leveraged the kinetic capability of this technology to gain insight into in-cell target residence time and the duration of target engagement, and to explore a structural hypothesis.